Genome-based reclassification of Paenibacillus dauci as a later heterotypic synonym of Paenibacillus shenyangensis. Issue 1 (21st November 2018) - Sant'Anna, Fernando Hayashi; Ambrosini, Adriana; Guella, Felipe Lhywinskh; Porto, Renan Zanini; Passaglia, Luciane Maria Pereira
Abstract : Paenibacillus shenyangensis and Paenibacillus dauci are Gram-stain-positive, rod-shaped and endospore-forming bacteria originally isolated from soil and carrot samples, respectively, in China. Preliminary comparative genomic analysis showed that these bacteria could constitute a single species. Therefore, in this study, their taxonomic statuses were clarified through distinct genomic metrics and phylogenetic analyses. Paenibacillus shenyangensis A9 T and P. dauci H9 T presented values of average nucleotide identity (ANI) and its derivative metrics (gANI and OrthoANI) ranging from 97.88 to 98.08 %, and digital DNA–DNA hybridization equal to 89.08 %. Furthermore, the identities of 16S rRNA, gyrB, rpoB, recA and recN genes were all equal or higher than 98.7 %. Phylogenies of these marker genes and the concatenated core proteome were congruent in the sense that P. shenyangensis A9 T and P. dauci H9 T are the closest type-strains of the genus Paenibacillus . A review of their profiles revealed that these strains do not present pronounced differences at the phenotypic and chemotaxonomic levels. Considering phylogenetic, genomic, phenotypic and chemotaxonomic data, P. dauci should be reclassified as a later heterotypic synonym of P. shenyangensis .